Validating a verbal autopsy tool to assess pre‐hospital trauma mortality burden in a resource‐poor setting. Issue 4 (12th March 2014) - Qureshi, Javeria S.; Samuel, Jonathan C.; Mulima, Gift; Kakoulides, Socrates; Cairns, Bruce; Charles, Anthony G.
Abstract Objectives To present the validation of a verbal autopsy (VA) tool using inpatient deaths in order to ultimately assess the burden of adult pre‐hospital trauma mortality in Lilongwe, Malawi. Methods A WHO VA tool was administered at the Kamuzu Central Hospital (KCH) morgue in Lilongwe to family members of inpatient deceased. Two physicians assigned cause of death as 'trauma' or 'non‐trauma' as well as a standard VA cause of death based on the VA tool. These assignments were compared to the 'gold standard' of physician review of hospital records using a kappa statistic. Results The VA method had near‐perfect agreement with the hospital record in determining 'trauma' vs. 'non‐trauma'. There was moderate agreement when comparing types of death, for example cardiovascular vs. infectious disease, and limited agreement when comparing specific causes of death. Conclusion This VA tool can accurately ascertain trauma‐related mortality with almost perfect agreement. The next step is to assess pre‐hospital trauma mortality burden using the VA tool to determine whether hospital records underestimate the burden of trauma in the community.